The experiences of health service providers working with children with physical disabilities and their caregivers in the Eastern Cape - Mathaba, Yollandah (Rhodes University, Faculty of Humanities, Department of Psychology, 2019)
The prevalence of childhood disability in South Africa is significant. In an attempt to meet the constitutional rights of children with disabilities, there are a variety of services available for children with disabilities. These services are aimed at rehabilitating children with disabilities and integrating them in society. Amongst such services are health services. Due to the nature of some childhood disabilities, it is recommended that they should be seen by a multidisciplinary team. While the field of childhood disability has been researched extensively. Limited research has been conducted on the experiences of health service providers working with children with disabilities and their caregivers. The current study explored the experiences of health service providers working with children with disabilities and their caregivers in the Eastern Cape. To achieve this aim, the study employed Interpretative Phenomenological Analysis (IPA). Five participants were recruited using purposive and snowball sampling methods. Semi-structured interviews were used to allow participants to freely share their experiences of working with children with disabilities and their caregivers. The interviews were audio recorded and transcribed for analysis purpose. The analysis process generated five master themes namely: Positive experiences of their work; negative experiences of their work; perception of their role as changing over time; managing challenges in their work; and experiences of a service learning programme as complementary to their work. The findings of the study highlighted both the positive experiences and the negative experiences of their work. On the one hand, the participants reported positive affect and that they found their work meaningful. They also reported a sense of feeling supported by fellow colleagues and enjoying their work at the clinics. On the other hand, the participants reported negative affect in relation to their wok difficulties such as feelings of frustration, feelings of being unappreciated by management and finding the work distressing. The participants reported that professional and emotional growth in conjunction with perspective taking contributed to developing better coping mechanisms. A service learning programme offered in the community was experienced as a good contribution to the work done at the clinics and distinguished as addressing the emotional needs of the caregivers which cannot be addressed at the clinics. The findings of the study supports and expands the literature on the experiences of health service providers working with children with disabilities in South Africa.
Keywords: Children with disabilities -- South Africa -- Eastern Cape; Caregivers -- South Africa -- Eastern Cape -- Case studies; Caregivers -- Psychology; Children with disabilities -- Care